The Authority of Autonomous Regions in The Formation of Regional Legal Products in The Unitary State of Indonesia System - Agnes Oktaviani Putri; Surahman Surahman; Imran Imran (Interdisciplinary Social Studies, 2026)
Indonesia, as a unitary state, adheres to a government system based on the principle of decentralization as mandated in the 1945 Constitution of the Republic of Indonesia. Through decentralization, the state grants autonomy to regions to regulate and manage certain governmental affairs, including the authority to create regional legal products as instruments for regulating regional autonomy. This authority is constitutionally legitimized in Article 18, paragraph (6) of the 1945 Constitution; however, it is not absolute, as it must remain within the framework of the Unitary State of the Republic of Indonesia and the national legal system, which is hierarchical. This research is normative legal research using a statutory, conceptual, and historical approach. The study analyzes the position and limits of the authority of autonomous regions in the formation of regional legal products, as well as the juridical problems that arise in practice. The results of the study indicate that regional legislative authority is a legitimate attribution of authority constitutionally, but it is limited by the principles of the unitary state, the hierarchy of legal regulations, the mechanisms of supervision and guidance from the central government. In practice, the formation of regional legal products still faces juridical problems, such as discrepancies between the material content and regional authority, the weak application of the principles of good legislative process, and the duality of supervision authority and harmonization between the Governor as the representative of the central government in the region and the Regional Office of the Ministry of Law and Human Rights.